PENERAPAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN 9 LIMBOTO - Vazriani K. Saleh; Mujahid Damopolii; Aljunaid Bakari (Al-mujahidah, 2026)
This study aims to determine the improvement of students' critical thinking skills in science learning using the discovery learning model in grade IV of SDN 9 Limboto. This type of research is classroom action research. The subjects in this study were 19 students of grade IV of SDN 9 Limboto. The objects in this study are the discovery learning model and students' critical thinking skills. This study was conducted in two cycles and each cycle had two meetings. Data collection techniques were carried out using observation and test techniques. The data analysis technique used in the study was descriptive statistics. Based on the results of the study, it can be concluded that the discovery learning model can improve students' critical thinking skills in science learning in grade IV. This is shown by the results obtained by students in the pre-cycle, cycle I and cycle II. In the pre-cycle, there were 7 students who were categorized as achieving KKTP with a percentage of 36% then increased in cycle I which was categorized as achieving KKTP as many as 10 students with a percentage of 52% and in cycle II increased to 16 students who achieved KKTP with a percentage of 84%. Thus, students' critical thinking skills and analysis of observation sheets improve in a better direction by applying the discovery learning model.